2018
DOI: 10.1002/celc.201800819
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Electrodeposition of Ni Metal and NiFe Hydroxide Composites with Heterogeneous Nanostructures as High Performance Multifunctional Electrocatalysts

Abstract: Water electrolysis provides an efficient method to produce hydrogen as clean energy source. Developing high activity electro‐catalysts towards the oxygen evolution reaction (OER) is crucial to improve the energy‐conversion efficiency of water electrolysis. In this work, heterogeneous nanostructures of NiFe hydroxide composites decorated by Ni metal were directly grown on a porous nickel foam (NF) substrate through an ultrafast electrodeposition process at a large cathodic current density of 1.5 A cm−2 within o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…It may be due to the thin layer of modified samples with poor crystalline and discontinuous lattice arrangements on the MS and discontinuous lattice arrangement of Fe and Ni hydroxide. It is similar to the recent observation of in-situ grown Fe(Ni)OOH catalyst on stainless steel substrate by Tang et al electrodeposited Ni and Fe hydroxide on carbon cloth by Zhuang et al and NiÀ Fe Oxide/ (Oxy)hydroxide on stainless steel support by Shen et al [13,22,23] In addition to this, surface chemical change was observed through Raman spectroscopy investigations also. Figure 3 shows the Raman spectra of MS, C MS, MS Ni(OH) 2 and C MS Ni(OH) 2 after OER cyclic sweep.…”
Section: Physico-chemical Characteristicssupporting
confidence: 89%
See 3 more Smart Citations
“…It may be due to the thin layer of modified samples with poor crystalline and discontinuous lattice arrangements on the MS and discontinuous lattice arrangement of Fe and Ni hydroxide. It is similar to the recent observation of in-situ grown Fe(Ni)OOH catalyst on stainless steel substrate by Tang et al electrodeposited Ni and Fe hydroxide on carbon cloth by Zhuang et al and NiÀ Fe Oxide/ (Oxy)hydroxide on stainless steel support by Shen et al [13,22,23] In addition to this, surface chemical change was observed through Raman spectroscopy investigations also. Figure 3 shows the Raman spectra of MS, C MS, MS Ni(OH) 2 and C MS Ni(OH) 2 after OER cyclic sweep.…”
Section: Physico-chemical Characteristicssupporting
confidence: 89%
“…electrodeposited Ni and Fe hydroxide on carbon cloth by Zhuang et al. and Ni−Fe Oxide/(Oxy)hydroxide on stainless steel support by Shen et al . In addition to this, surface chemical change was observed through Raman spectroscopy investigations also.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, it is prospective to become the power source of mobile stations and fuel cell vehicles. Therefore, non-precious metals such as Cu, [18][19][20][21] Fe, [22] Co, [23][24][25] Ni [26][27][28][29] based alloys have attracted many attentions due to their high conductivities, low costs, and most importantly good catalytic activities. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] Among those, noble metals such as Au, [10,11] Pd, [12,13] Pt [14,15] and Ag [16,17] exhibit relatively better catalytic properties and slower self-decomposition rates.…”
Section: Introductionmentioning
confidence: 99%